2004
DOI: 10.1017/s0021932004006789
|View full text |Cite
|
Sign up to set email alerts
|

Family Formation and Dissolution in an Aegean Island

Abstract: This paper explores family formation and dissolution in the Aegean island of Paros over the period 1894–1998. The examined issues are: trends in age at marriage, age gap between spouses, age differentials among different occupational groups, age at widowhood, remarriage, illegitimacy and bridal pregnancy. The main findings confirmed that certain characteristics of the ‘Mediterranean’ marriage pattern, such as low age at marriage for females, high for males and large age gap between spouses, were present in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Similar results have been found in smaller, geographically localized populations. Gavalas (2005) found that the relevant figures for Naoussa and Kostos (Paros Island) were around 2% at the beginning, and 0.3% by the end of the 20 th century. Hionidou (1993) found the rate of illegitimate births in Mykonos to be below 2% (mid-19 th until mid-20 th centuries).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results have been found in smaller, geographically localized populations. Gavalas (2005) found that the relevant figures for Naoussa and Kostos (Paros Island) were around 2% at the beginning, and 0.3% by the end of the 20 th century. Hionidou (1993) found the rate of illegitimate births in Mykonos to be below 2% (mid-19 th until mid-20 th centuries).…”
Section: Discussionmentioning
confidence: 99%
“…Zafeiris (2010) studied several aspects of the marriage system based on marriage cohorts in a large sample from the Department of Rhodopi (Greek Thrace). From the point of view of historical demography, apart from some papers concerning island populations, such as for example those of Hionidou (1993) and Gavalas (2002Gavalas ( , 2005Gavalas ( , 2008, other approaches, though not strictly demographic, focused on mainland Greece, including for example those of Bournova (1995) for Rapsani andCaftanzoglou (1994, 1997) for Syrrako.…”
Section: Introductionmentioning
confidence: 99%
“…According to observations, the woman most often organically and easily perceives new responsibilities -wife, mother, housewife (Zerle, Cornelißen and Bien 2012). The man continues to search for the meaning of life, the formation of his personality lasts longer (Gavalas 2005). For a woman, marriage is, first of all, a safe, secure home and everything connected with it (Keim, Klärner and Bernardi 2013): material well-being, protection, romantic appeal, affection and the opportunity to become a mother; for a man, marriage is sexual satisfaction, a woman's care, and only then the need to provide for a family and support the mother of his children.…”
Section: Introductionmentioning
confidence: 99%